Sustainability materiality of insuring coal businesses for insurers - Umakanth, Mithula (Frontiers in Sustainability, 2024)
This study aims to understand the impact of sustainability efforts on materiality or financial performance of insurers by accounting their risk coverage pattern in the Coal Mining Industry. 10 major insurance companies have been selected for this study and the focus has been to understand the stances and policies implemented by these companies between 2018 and 2023. Some of the firms like Hartford have officially declared that they have exited from this industry, while major players are still fueling the coal mining industry. Alternatively, companies themselves are looking to fund their risk mitigation plans so as to not rely on insurance firms. Studies by Hinshaw Law show that losses arising from climate change are rising at an alarming rate, the question then remaians, would insurance companies continue to fund activities that would put their existence in peril. Further research can be conducted on a larger time frame, new policies and frameworks implemented across this industry and to understand the risks of insuring activities that have increased the rate of climate change.